Semiotic Analysis of Da'wah Messages in the Lyrics of the Song " Jangan Berputus Asa " Syubbanul Muslimin Probolinggo to Affirm Islam - Romadlany, Zakiyah; Abidhin, Moch Zayyil (Studi Multidisipliner: Jurnal Kajian Keislaman, 2024)
Da'wah is a tool for conveying religious messages. Like any tool, da'wah has a clear target or objective, which is to guide the community toward goodness. Over time, numerous methods have been developed to convey da'wah messages, one of which is through music or songs. While many religious leaders deliver da'wah from pulpits and in places of worship, there are also those who choose to communicate da'wah messages through poetic lyrics accompanied by harmonious melodies, commonly referred to as religious songs. This study explores the role of songs in conveying da'wah messages, with a focus on a song by Syubbanul Muslimin from the album Kidung Surgawi titled "Jangan Berputus Asa" ("Do Not Despair"). The study aims to examine how da'wah lyrics within the song contribute to listeners' understanding of the meaning and messages conveyed. Using Charles Sanders Peirce's semiotic method, the author analyzes the song with a descriptive approach through the words in the lyrics, interviews with members of Syubbanul Muslimin, and data collected from media platforms. This study reveals that the song Jangan Berputus Asa carries a message encouraging people to always be grateful for Allah blessings, especially the spirit to keep striving for His approval. It reminds us to be aware of the ups and downs of life and to  belief that everything is determined by Allah and always contains wisdom behind it. The essence is to accept everything with gratitude, sincerity, patience, and resilience. Moreover, it serves as a motivational boost for us to keep moving forward.